2023
DOI: 10.1021/acs.jnatprod.3c00382
|View full text |Cite
|
Sign up to set email alerts
|

Persephacin Is a Broad-Spectrum Antifungal Aureobasidin Metabolite That Overcomes Intrinsic Resistance in Aspergillus fumigatus

Lin Du,
Saikat Haldar,
Jarrod B. King
et al.

Abstract: Fungi pose a persistent threat to humankind with worrying indications that emerging and re-emerging pathogens (e.g., Candida auris, Coccidioides spp., drug-resistant Aspergilli, and more) exhibit resistance to the limited number of approved antifungals. To address this problem, our team is exploring endophytic fungi as a resource for the discovery of new antifungal natural products. The rationale behind this decision is based on evidence that endophytes engage with plants in mutualistic relationships wherein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…In another study, Persephacin, isolated from the endophytic fungus Sphaceloma sp., showed activity against a diverse range of fungal species ( C. albicans , C. glabrata , C. parapsilosis , C. krusei , C. kefyr , C. tropicalis, and C. auris ). Persephacin resulted in MIC values around 2.5 µg/mL, which was similar to the activity expressed by AmB [ 65 ]. A group of new linear lipopeptides (Myropeptin C–E and Myropeptin A1), isolated from the saprotrophic filamentous fungus Myrothecium inundatum , showed good inhibition of C. auris cells.…”
Section: Therapeutic Optionssupporting
confidence: 52%
“…In another study, Persephacin, isolated from the endophytic fungus Sphaceloma sp., showed activity against a diverse range of fungal species ( C. albicans , C. glabrata , C. parapsilosis , C. krusei , C. kefyr , C. tropicalis, and C. auris ). Persephacin resulted in MIC values around 2.5 µg/mL, which was similar to the activity expressed by AmB [ 65 ]. A group of new linear lipopeptides (Myropeptin C–E and Myropeptin A1), isolated from the saprotrophic filamentous fungus Myrothecium inundatum , showed good inhibition of C. auris cells.…”
Section: Therapeutic Optionssupporting
confidence: 52%
“…In another study, Persephacin isolated from the endophytic fungus Sphaceloma sp showed activity against a wide spectrum of fungal species (C. albicans, C. glabrata, C. parapsilosis, C. krusei, C. kefyr, C. tropicalis and C. auris). Persephacin resulted in the MIC values around 2.5 µg/mL, which was equal to the activity expressed by Amp B [64]. A group of new linear lipopeptides (Myropeptin C−E and Myropeptin A1) isolated from saprotrophic filamentous fungus Myrothecium inundatum, also produced good inhibition in C. auris cells.…”
Section: Natural Products Against Candida Aurismentioning
confidence: 84%
“…In this context, remarkable progress is being made in the development of new bioactive compounds against phytopathogens such as FOX on a weekly basis. [10][11][12][13][14][15][16][17][18] However, many of these advancements come with a signicant drawback. Most active compounds are derived from natural sources, resulting in limited quantities that make it challenging to conduct thorough testing and eld evaluations.…”
Section: Introductionmentioning
confidence: 99%